2017
DOI: 10.18632/oncotarget.19071
|View full text |Cite
|
Sign up to set email alerts
|

Expression and clinical association of programmed cell death-1, programmed death-ligand-1 and CD8+ lymphocytes in primary sarcomas is subtype dependent

Abstract: In order to explore the potential of immune checkpoint blockade in sarcoma, we investigated expression and clinical relevance of programmed cell death-1 (PD-1), programmed death ligand-1 (PD-L1) and CD8 in tumors of 208 sarcoma patients. Primary untreated osteosarcoma (n = 46), Ewing sarcoma (n = 32), alveolar rhabdomyosarcoma (n = 20), embryonal rhabdomyosarcoma (n = 77), synovial sarcoma (n = 22) and desmoplastic small round cell tumors (DSRCT) (n = 11) were examined immunohistochemically. PD-L1 expression w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
63
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(73 citation statements)
references
References 40 publications
5
63
0
1
Order By: Relevance
“…[33][34][35] Numerous studies have evaluated the expression of PD-L1 in DSRCT and synovial sarcoma with conflicting results. While some authors reported high levels of PD-L1 in DSRCT tissue 20,36 and in synovial sarcoma, 18 in contrast, and consistent with our findings, two other groups reported very low or no expression of PD-L1 in either tumor type. 19,37 We observed extensive heterogeneity of PD-L1 expression within each tumor type, which might explain the disparate reports.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…[33][34][35] Numerous studies have evaluated the expression of PD-L1 in DSRCT and synovial sarcoma with conflicting results. While some authors reported high levels of PD-L1 in DSRCT tissue 20,36 and in synovial sarcoma, 18 in contrast, and consistent with our findings, two other groups reported very low or no expression of PD-L1 in either tumor type. 19,37 We observed extensive heterogeneity of PD-L1 expression within each tumor type, which might explain the disparate reports.…”
Section: Discussionsupporting
confidence: 92%
“…Most of these studies show conflicting data on expression levels and clinical outcomes. [17][18][19][20] Whether immunotherapies for DSRCT and synovial sarcoma will be useful is currently unknown. Numerous results from other cancer subtypes suggest that expression of relevant immunologic molecules and intratumoral immune cell infiltrates may be predictive of prognosis and therapeutic response.…”
Section: 2 Standard Treatment For Dsrct Consistsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, osteosarcoma cells express B7-H3 which is correlated with the aggressiveness of the disease and metastatic capacity [85,86]. Program Death Ligand-1 (PDL-1) and PDL-2 were also detectable in all osteosarcoma cases [89][90][91][92][93][94].…”
Section: Lymphocytes Subpopulations In Osteosarcoma and Therapeutic Imentioning
confidence: 99%
“…However, because these studies comprised a small number of patients with SS, the expression of PD-L1 in SS and its clinical significance remain controversial. [17][18][19][20][21] Understanding how the tumor immune microenvironment relates to the prognosis of patients with SS may clarify the potential for effective immunotherapy for the treatment of SS. However, to the best of our knowledge, the tumor immune microenvironment including TILs, macrophages, and the expression of HLA class I and PD-L1 are not well understood in SS.…”
mentioning
confidence: 99%